Gaya Bahasa Penyuluh Agama Dalam Berdakwah Terhadap Masyarakat Plural - Maulida Fitri; Siti Masturoh (Jurnal Dakwah dan Komunikasi, 2020)
Indonesia has a variety of cultures so that it makes a plural society. With this diversity, it is a challenge for religious educators to use a style of language that is in accordance with the characteristics of a plural society. This article, which uses a qualitative descriptive approach, aims to look at the various styles of language that can be used by religious instructors. The results show that preachers should use qaulan ma'rufa or good words, qaulan sadida or true words, qaulan baligha or words that leave an impression, qaulan maysura or noble words, qaulan karima, namely communicating using noble words and qaulan layyina , communicating with a gentle attitude towards a plural society.